Geochronology, petrogenesis and tectonic implications of the early Cretaceous granitoids in the Jingde-Guangde area, Anhui province, South China. (1st April 2020) - Yue, Qian; Yan, Jun; Liu, Jianmin; Xie, Jiancheng; Li, Quanzhong; Luo, Qiankun
Graphical abstract: Highlights: Granitoids in the Jingde-Guangde area formed in two stages: 152–135 Ma and 135–130 Ma. Early and late stages were identified to be I-type and I-A transform-type respectively. Two stages granitoids were formed under different temperatures and oxygen fugacities. Both granites were derived from Neoproterozoic crust. The driving force of two igneous events was the paleo-Pacific subduction. Abstract: The eastern Jiangnan Orogen comprises two tectonic units: the initial defined Jiangnan Orogen (IJO) and the eastern extension area of the Jiangnan Orogen (EEJO). Ten granitoid intrusions with ages from 152 to 130 Ma in the EEJO, were selected for integrated studies. Therein, I-type granodiorites and monzogranites (152–135 Ma) had SiO2 contents of 62.5–69.0 wt%, total alkali contents of 6.2–7.9 wt%, and a narrow range of A/CNK (0.91–1.03). They also showed enrichment of LILE, depletion in HFSE, slightly Eu negative anomalies. I-A transform-type monzogranites and K-feldspar granites (135–130 Ma) exhibited a systematic higher SiO2 (64.6–74.5 wt%) and total alkali contents of 7.8–10.1 wt%, but low Al2 O3 (13.42–15.75 wt%), Fe2 O3 T (1.29–4.00 wt%), MgO content (0.16–1.32 wt%) with more significant Eu and Sr negative anomalies. Whole rock εNd (t) and 87 Sr/ 86 Sr(t) values of the granodiorite-monzogranites fall into the ranges of −8.8 to −6.1 and 0.7080–0.7112, respectively. Their εHf (t) and δ 18 O values are from −11.4 to −3.1 and 7.12‰ to 10.03‰. The monzogranites and K-feldspar granites show relatively higher εNd (t) values (−6.1 to −5.4) and narrow 87 Sr/ 86 Sr(t) ratios (0.7086–0.7104). Their εHf (t) and δ 18 O values range from −9.3 to −3.3 and 7.23‰ to 10.09‰. These rocks dominantly derived from partial melting of the early Neoproterozoic accretionary crust, indicating that the EEJO should belong to the Jiangnan Orogen. The presence of I-A transform-type rocks implies that the tectonic geodynamic frame transformed from compression to extension might have took place at 135 Ma.